Osteoperiosteal Decortication and Autogenous Cancellous Bone Graft Combined with Bridge Plating for Non-hypertrophic Diaphyseal Nonunion - Cho, Youngho; Byun, Young-Soo; Suh, Jeong-Duk; Yoo, Junhyug (Clinics in orthopedic surgery, 2021)
The aim of this study was to evaluate results of osteoperiosteal decortication and autogenous cancellous bone graft combined with a bridge plating technique in atrophic and oligotrophic femoral and tibial diaphyseal nonunion. We retrospectively reviewed 31 patients with atrophic or oligotrophic femoral and tibial diaphyseal nonunion treated with osteoperiosteal decortication and autogenous cancellous bone graft between January 2008 and December 2018. Patients with hypertrophic nonunion, infected nonunion, and nonunion treated with autogenous cancellous bone graft alone were excluded. The nonunion site was exposed by using the Judet technique of osteoperiosteal decortication. Nonunion with a lack of stability was stabilized with a new plate using a bridge plating technique or augmented by supplemental fixation with a plate. Nonunion with malalignment was stabilized with a new plate after deformity correction. Autogenous cancellous bone graft was harvested from the posterior iliac crest and placed within the area of decortication. A basic demographic survey was conducted, and the type of existing implants, mechanical stability of the implants, the type of implants used for stabilization, the operation time, the time to bone union, and postoperative complications were investigated. The average follow-up period was 33.3 months (range, 8-108 months). The operation time was 207 minutes (range, 100-351 minutes). All but 1 nonunion (96.7%) were healed at an average of 4.2 months (range, 3-8 months). In 1 patient, bone union failed due to implant loosening with absorbed bone graft, and solid union was achieved by an additional surgery for stable fixation with a new plate, osteoperiosteal decortication, and autogenous cancellous bone graft. There were no other major complications such as neurovascular injuries, infection, loss of fixation, and malunion. Osteoperiosteal decortication and autogenous cancellous bone graft combined with stable fixation by bridge plating showed reliable outcomes in atrophic and oligotrophic diaphyseal nonunion. This treatment modality can be effective for treating atrophic and oligotrophic diaphyseal nonunion because it is very helpful stimulating bone union.